1993
DOI: 10.1111/j.1472-765x.1993.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods to demonstrate the bactericidal activity of bacteriocins

Abstract: Two simple techniques were developed to demonstrate bactericidal activity of bacteriocins. Both were based on allowing a lawn of indicator strain to grow first, then exposing the lawn to bacteriocin-containing cell-free supernatants in a well cut in the seeded agar lawn or by inoculating the bacteriocin-producing strain onto the indicator lawn. Lysis of cells of the indicator strain resulted in a clear zone. These techniques may be adapted to test antimicrobial substances other than bacteriocins and to help to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…The 180 isolates examined here were screened for inhibitory activity by using a spot-lawn method (25) at 25°C under aerobic conditions. Thirtynine of the isolates showing inhibition (effectors) were selected, representing different species, abattoirs, storage times, and bacterial genera (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 180 isolates examined here were screened for inhibitory activity by using a spot-lawn method (25) at 25°C under aerobic conditions. Thirtynine of the isolates showing inhibition (effectors) were selected, representing different species, abattoirs, storage times, and bacterial genera (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The spot-lawn agar method (25) has been widely used to detect bacterial inhibitory activity, via reporting an inhibition zone (8,26,27). However, this method does not supply specific information about the effect of an effector on target growth, such as that achieved using broth-based assays.…”
mentioning
confidence: 99%
“…Indeed, these methods allowed the standardization of the inoculum, making possible the comparison between diameters of the inhibition zones (29). Benkerroum et al (2) had concluded that this method is suitable and designated lyse zones as opposed to the spot-onthe-law method. The lyse zones could be seen after 3 h of incubation by wells diffusion method, while 48 h were necessary to see definitive inhibition zones by the spot test assay or streak inoculation.…”
Section: Screening For Antibacterial Activitymentioning
confidence: 99%
“…The well diffusion direct assay described by Tagg and McGiven (29) and modified by Benkerroum et al (2) was utilized to detect the bacteriocinproducing strains. The GM17 broth was supplemented with sodium β-glycerophosphate (2%) and catalase (Sigma Chemical Co., Dorset, England) at final concentration of 100U.…”
Section: Detection Of Antagonistic Activitymentioning
confidence: 99%
“…In a first test series, the ability of each of the Lactobacillus isolates to exert an antibacterial effect against Listeria monocytogenes ATCC 19115 and Salmonella Typhimurium PTCC 1186 were examined by using three methods: the spot-on-lawn method, standardized agar disk diffusion method and the well diffusion method as described by Schillinger and Lucke [33], Benkerroum et al [34] and Tagg & Mc Given [35]. Throughout, cell-free supernatants (CFS) of strains were obtained by centrifugation at 10,000 ×g for 20 min and then adjusted to pH 6.5 by applying NaOH (to exclude the effect of organic acid) before sterilization by filter (0.2 µm, Sigma, UK).…”
Section: Screening Of Lactobacillus Strains For Their Inhibitory Potementioning
confidence: 99%